FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KUALITAS PEMERIKSAAN PAJAK DI INDONESIA - Daris, Fiki Taufik; Winarningsih, Srihadi; Devano, Sony (Universitas Muhammadiyah Palembang, 2021)
The self assessment system require Directorate General of Taxation to conduct supervision of taxpayers effectively. One form if supervision is a tax audit which aims to assess the compliance of tax obligation. With limited resouces, DGT must cary out the good quality audits to be proper on target and have a broad impact on escalate tax compliance and revenue. The implementation and results of tax audit must be accountable and reliable in the eyes of stakeholders. This research is carried out with quantitative method using multiple regression analysis statistical test to determine how the effect of risk-based audit implementation, competence, professional skepticism, and the use of information technology on the quality of tax audits. The results of this study indicate that the variables of competence and utilization of information technology have an effect on the quality of tax audits, while the variables of riskbased audit implementation and professional skepticism have no effect toward the quality of tax audits. Simultaneously all the variables x affect the quality of tax audits